Environmental Education and Ecotourism for Sustainable Life: Literature Study - Aswita, Dian (Jurnal Ilmiah Peuradeun, 2018)
This study discusses the results of the research related to ecotourism and environmental education in relation to sustainable life. This study is a literature study. Data were obtained from articles and books related to environmental education and ecotourism and were analyzed using qualitative descriptive analysis techniques. The results show that the purpose of environmental education is to teach and educate the public about natural environment and ecosystems in order to sustain life. Ecotourism and environmental education are inseparable and must be mutually supportive. Ecotourism development requires environmental education as the base, as much as a tourist area can be used as a source for learning about environment for everyone. Environmental education is intended to improve knowledge about environment which encourages attitude and pro-environmental behaviors, as well as having a positive attitude towards ecotourism and environmental conservation. There is a strong positive correlation between environmental knowledge and people's attitudes towards ecotourism. The study shows that there was a positive correlation of 0.70, which confirms that environmental knowledge (EK) positively influences youth’s attitude towards ecotourism (EA).